Multiple Interest Rate Analysis: Theory and Applications - Osborne, Michael. (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
This book is an analysis of all possible interest rates. Dual expressions are used to solve long-standing puzzles, eliminate anomalies and draw conclusions about best practice and sound policy advice in areas of economics and finance. Topics include retail and corporate finance, capital budgeting and investment appraisal, bond risk management. An on-line model demonstrating ideas from the book is available in the Wolfram Demonstrations Project (WDP) by searching "multiple interest rate analysis" in the WDP search engine. A 'computable document' containing the model and the model's code are also available as free downloads from the site.